O olhar sobre a prática na construção da identidade do enfermeiro: imagem do estranhamento dos novos cenários de aprendizagem - Souza, Marilei de Melo Tavares e (2009)
This study sought to identify potential artistic/creative in nursing students, based on perceptions of the learning scenario. There was an exploratory descriptive qualitative approach, ten students from the Nursing Course, University Severino Sombra, Brooms, State of Rio de Janeiro. The study was conducted by an instrument in which the subjects express poetically experiences in learning scenarios. We tried to identify in this study looks launched by academics about their practice and capture images of the strangeness of new learning scenarios, in building their professional identity. Based on the material analyzed, we attempted to expand the senses to form a mosaic of knowledge about the education experience of nursing practice. The images designed by students for experiments with the learning scenario revealed that the daily nursing care is perceived as critical and poetic, and emotional commitment. Students recall the emotion, sensitivity and creativity in the educational process, which refers to reflective practice in nursing. The images analyzed speak of commitment to freedom, subjective life and work. It follows that the education of feeling and appreciation of creativity are key to nursing education as its object of interest is the life of the individual and the community. Thus, the nursing curriculum should talk to artistic assumptions, highlighting the experience as a basic form of knowledge